A dimensão ética da Ontologia da atualidade de Gianni Vattimo - Maia, Antonio Glaudenir Brasil (2010)
This dissertation investigates the ethical dimension as a fundamental premise of today s ontology as proposed by Gianni Vattimo, arguing that the ethics constitute a strong motivation of his philosophical thought and even of the further readings that Vattimo produces on politics, aesthetic, religion, among other relevant issues related to the postmodern condition. This way, the main objective is to explain that, since the announcement of the pensiero debole [1983], the route walked by Vattimo until the present has the ethics as the recurrent subject in his various texts. Considering this, it is defended that Vattimo s speech strives to posit a close implication between the ethics instance and criticism of the Metaphysics, with a speech that refuses, beside Heidegger and Nietzsche, the logic of metaphysical foundations, toward reasons strictly ethical. As a bibliographical research, the books were selected by their closeness with the definition of the general lines of research and, appropriately, met an exposition method of the conceptual movement that unifies most of the sources used. The originality of the thesis was traced based on assertion of ethics as a fundamental dimension of the ontology dell attualità vattimiana. This premise was not sufficiently researched by the philosophical literature and, despite the fact that the issue of ethics has already addressed on Vattimo thought, the previous researches were restricted to works published, by Vattimo himself, on the subject (ethics). Here the proposal was not limited to the interpretative analysis of the works that dealt directly with the problems of ethics. Therefore, Vattimo s description of his today's ontology is inspired essentially in the ethical problem, because he shows, in his reflections, a total dissatisfaction with the political, ethical, religious, social, aesthetic situations, making the ethical reason the sole serious reason for Philosophy.